Physico-chemical properties of galfenols obtained on the basis of a powder alloy Fe-21.5 (wt.%) Ga - Honcharuk, Dmytro; Bahliuk, Gennadii; Khomenko, Olekcii; Khomenko, Olena (Physics and Chemistry of Solid State, 2026)
The properties of magnetostrictive materials developed on the Fe-Ga powder alloy, which is an analogue in composition of industrial galfenols - the newest materials used on underwater communications, were determined. Binary and ternary alloys obtained by forming and sintering powder mixtures of the basic composition (Fe-21.5 (wt.%) Ga), as well as with the addition of dispersed particles of carbide or nitride or titanium diboride to this mixture of strengthening powders, were studied. Powdered galfenols have high mechanical properties under compression conditions (yield (conditional) and strength limits reach up to 999 MPa and up to 1447 MPa, respectively). The electrical resistance of those ranges from 55 to 67 μΩ·cm, corresponds to the average level of electrical resistance of industrial galfenols (60–80 μΩ·cm). The magnetostriction coefficients of materials are 210 ppm (basic composition), 180 ppm (basic composition + 5 (vol.%) TiB₂) and 160…165 ppm (basic composition + 5 (vol.%) TiC; basic composition + 5 (vol.%) TiN), fully satisfies the requirements for industrial galfenols. Powder galfenol of the basic composition exhibits the greatest corrosion resistance in an environment imitating sea water and, according to the classification of the 10-point scale of corrosion resistance, belongs to the group of corrosion-resistant materials (4 points). Ternary galfenols have lower corrosion resistance and, have lower corrosion resistance and, depending on their composition, can be classified as moderately resistant materials (5-6 points).